Actor engagement in online communities: a practice-based approach - El Kolaly, Hoda (2018)
Despite extensive interest by academics and practitioners to understand and harness actor engagement (AE), empirical work offering insights into how and why actors change their engagement over time are limited and extant empirical research mostly focuses on the individual level of AE and fails to address its social aspects and the effects of A2A interactions. Therefore, this research is a response to both a managerial and a theoretical need for a deeper understanding of the dynamics of the AE process in an online community, while accounting for the social aspects of AE and the effects of A2A interactions. Drawing on practice theory, this thesis sets out to explore the dynamics of engagement through the engagement practices of members in an online community, identify the full spectrum of engagement states, and changes in such states over time. The objectives of this study are twofold. First, to advance the conceptualisation of AE by adopting a practice-based approach. Second, to demystify the dynamics of the AE process and the effects of A2A interactions on such a process. The context of the study is the for-profit community ExpatWoman.com (www.expatwoman.com), which is independently owned and funded mainly by advertising. The researcher’s philosophical stance is that of a social constructivist, hence social constructivism is the paradigm underpinning this thesis. To achieve the above two aims, the methodology of netnography is deemed suitable to study the selected online community, where non-participant observation of the Dubai forum is used and complemented by participant observation of offline meetups organised by the community. Summarising the main implications for theory and practice, this thesis contributes from a theoretical perspective by enriching and advancing our understanding of AE in the context of online communities in four ways. First, it advances the AE conceptualisation by adopting a practice-based approach, hence supplementing its S-D logic-based foundational perspective with practice theory and demonstrates that the latter can provide a useful lens for empirically exploring AE. Second, it enhances the AE dimensionality by providing empirical support for the need to include a fourth (social) dimension. Third, by using longitudinal data, this study is one of the first to empirically explore the dynamics of the AE process in an online community and to provide empirical evidence of the engagement conceptualisation proposed by Chandler & Lusch (2015) as comprising of two fundamental attributes: connections and dispositions. Fourth, unlike most of engagement studies to date, this research considers not only positive relationships but also negative experiences, and further explores the under-researched concept of disengagement by differentiating between naturally occurring and induced disengagement. As for the practical contributions, the managerial implications emerging from the findings are primarily relevant for the growth and survival of online communities as well as for starting one. It also presents a better understanding of AE that can better guide the development of organisational strategies and tactics to maximise the benefits of this highly promising concept. Therefore, this thesis aims at suggesting some tactics to better manage the engagement platforms in specific, and the engagement process in general in the context of online communities. It also responds to calls to explore AE outside the more established B2C setting (e.g. Hollebeek et al. 2016a) and contribute to the wider online community literature by focusing on a community of interest, which represents a substantial proportion of online communities and which has been under-explored in comparison to the more researched brand communities (Hartmann et al. 2015; Weijo et al. 2014), hence can allow marketers to better capitalise on the significant opportunities that such communities can present.